(3aJM GdbOjQs - (3ceGd GdOjf eMeO Hf YHO GdhGMO Hf YHO GdMejO Hf GdgeGe GdSjhGSj GdEScfOQj, GdceGd Hf GdgeGe,J (B861 (3g` s ((3eMeO Hf CMeO GdLQhGfi GdCRgQj GdeGdci s)
(3ChdgG (B:s
(3cJGH GdQLYI hLg GdefGSHI ai GYbGH GdWdGb HGdQLYI XGgQ s
(3BNQgG (B:s
(3Je GdcJGHGdeHGQc HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B134s
Keywords: (3Gdabg GdMfajs